2022
DOI: 10.2147/dmso.s389327
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride Glucose Index is Related with the Risk of Mild Cognitive Impairment in Type 2 Diabetes

Abstract: Background The triglyceride glucose (TyG) index reflects insulin resistance; the latter being associated with mild cognitive impairment (MCI). Objective To investigate the clinical value of the TyG index to identify MCI in patients living with type 2 diabetes (T2D) using a cross-sectional study. Methods This cross-sectional study was performed on 517 patients with T2D. The diagnosis of MCI was based on criteria established by the National Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 61 publications
0
15
1
Order By: Relevance
“…20,21 Another study found that in participants with type 2 diabetes, the TyG index could be used to predict the risk of developing mild cognitive decline. 22 In the present study, we found that participants with MetS had a 50% increase in odds of poor speed of reaction scores, although this change was not statistically significant . This finding is consistent with that of a previous study that reported an association between MetS and poor speed of reaction in the elderly.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…20,21 Another study found that in participants with type 2 diabetes, the TyG index could be used to predict the risk of developing mild cognitive decline. 22 In the present study, we found that participants with MetS had a 50% increase in odds of poor speed of reaction scores, although this change was not statistically significant . This finding is consistent with that of a previous study that reported an association between MetS and poor speed of reaction in the elderly.…”
Section: Discussioncontrasting
confidence: 62%
“… 20 , 21 Another study found that in participants with type 2 diabetes, the TyG index could be used to predict the risk of developing mild cognitive decline. 22 …”
Section: Discussionmentioning
confidence: 99%
“…1. Consequently, a total of ten studies were deemed suitable for subsequent meta-analysis [18][19][20][21][22][23][24][25][26][27].…”
Section: Literature Search and Study Inclusionmentioning
confidence: 99%
“…Overall, ten observational studies, including one prospective cohort study [26], three retrospective cohort studies [19,20,23], and six cross-sectional studies [18,21,22,24,25,27], were included in the meta-analysis. The characteristics of the included studies are summarized in ▶ table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation